Critical Role of Neprilysin in Kidney Angiotensin Metabolism. Issue 5 (14th August 2020) - Kaltenecker, Christopher C.; Domenig, Oliver; Kopecky, Chantal; Antlanger, Marlies; Poglitsch, Marko; Berlakovich, Gabriela; Kain, Renate; Stegbauer, Johannes; Rahman, Masudur; Hellinger, Roland; Gruber, Christian; Grobe, Nadja; et al.
Abstract : Rationale: Kidney homeostasis is critically determined by the coordinated activity of the renin-angiotensin system (RAS), including the balanced synthesis of its main effector peptides Ang (angiotensin) II and Ang (1–7). The condition of enzymatic overproduction of Ang II relative to Ang (1–7) is termed RAS dysregulation and leads to cellular signals, which promote hypertension and organ damage, and ultimately progressive kidney failure. ACE2 (angiotensin-converting enzyme 2) and NEP (neprilysin) induce the alternative, and potentially reno-protective axis by enhancing Ang (1–7) production. However, their individual contribution to baseline RAS balance and whether their activities change in chronic kidney disease (CKD) has not yet been elucidated. Objective: To examine whether NEP-mediated Ang (1–7) generation exceeds Ang II formation in the healthy kidney compared with diseased kidney. Methods and Results: In this exploratory study, we used liquid chromatography-tandem mass spectrometry to measure Ang II and Ang (1–7) synthesis rates of ACE, chymase and NEP, ACE2, PEP (prolyl-endopeptidase), PCP (prolyl-carboxypeptidase) in kidney biopsy homogenates in 11 healthy living kidney donors, and 12 patients with CKD. The spatial expression of RAS enzymes was determined by immunohistochemistry. Healthy kidneys showed higher NEP-mediated Ang (1–7) synthesis than Ang II formation, thus displaying a strong preference towards the reno-protective alternative RAS axis. In contrast, in CKD kidneys higher levels of Ang II were recorded, which originated from mast cell chymase activity. Conclusions: Ang (1–7) is the dominant RAS peptide in healthy human kidneys with NEP rather than ACE2 being essential for its generation. Severe RAS dysregulation is present in CKD dictated by high chymase-mediated Ang II formation. Kidney RAS enzyme analysis might lead to novel therapeutic approaches for CKD. Abstract : Supplemental Digital Content is available in the text.